Kinderlager der Arbeiterkinderhilfe: Mädchen und eine Betreuerin posieren vor dem Haus
internationale Politik (allgemein);internationale Beziehungen;Entwicklungszusammenarbeit;Hilfswerk soziale Fragen;sozialer Schutz;Sozialpolitik;Kinderbetreuung